Accuracy of Conventional Instrumentation is Dependent on Alignment Philosophy Using the Identical Surgical Technique in Total Knee Arthroplasty - Koutp, Amir; Clar, Clemens; Leitner, Lukas; Fischerauer, Stefan; Reinbacher, Patrick; Leithner, Andreas; Klasan, Antonio; Sadoghi, Patrick (The Journal of Knee Surgery, 2023)
The objective of this prospective study was to assess the precision of restoring the anatomical tibial obliquity, as measured by the medial proximal tibial angle (MPTA) on conventional X-rays, in relation to the surgical technique employed. Specifically, the study aimed to compare the accuracy of tibial obliquity restoration between kinematic alignment (KA) and conventional mechanical alignment (MA) in total knee arthroplasty (TKA). Two-hundred-and-sixty patients underwent either mechanically aligned TKA (n = 139) or kinematically aligned TKA (n = 121) using conventional instrumentation (CI). Pre- and postoperative X-rays were measured twice by two observers, with a 2-week interval. Inter- and intraclass correlations were calculated, and postoperative tibial obliquity was compared to the preoperative anatomy. In the group of 139 patients with mechanically aligned TKA, no cases with an MPTA deviation greater than 1 degree from 90 degrees were observed. Sixteen percent of the cases (n = 22) had a deviation of 0 to 1 degree. The remaining 84% of the cases (n = 117) had their MPTA of 90 degrees achieved. In the group of 121 patients with kinematically aligned TKA, no cases had a deviation greater than 1 degree compared with the preoperative MPTA. Thirty-one percent of the cases (n = 37) had a deviation of 0 to 1 degree with respect to preoperative MPTA. The remaining 69% of the cases (n = 84) had their tibial obliquity restored. Mechanically aligned TKA revealed statistically significant smaller deviations of accuracy compared to kinematically aligned TKA (p = 0.005). The inter- and intraclass correlations indicated substantial agreement of all measurements (intraclass correlation coefficient [ICC] < 0.90). Both mechanically aligned and kinematically aligned TKA demonstrated satisfactory outcomes in terms of restoring tibial obliquity or a neutral MPTA of 90 degrees using CI. However, MA showed superior results regarding precision compared to KA. When starting with kinematical alignment using CI, the surgeons should be aware that the learning curve according to accuracy differs to MA. It was a Prospective Level II study.
Keywords: total knee arthroplasty; tibial obliquity; MPTA; kinematic alignment; mechanical alignment